2022
DOI: 10.3389/fped.2022.842544
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a common occurrence in the neonatal intensive care unit (NICU). In recent years, our knowledge of the incidence and impact of neonatal AKI on outcomes has expanded exponentially. Neonatal AKI has been shown to be associated with adverse outcomes including increased length of mechanical ventilation, prolonged length of stay, and rise in mortality. There has also been increasing work suggesting that neonates with AKI are at higher risk of chronic kidney disease (CKD). In the past, AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 99 publications
0
41
0
Order By: Relevance
“… 5 , 6 , 7 , 8 , 9 Short-term mortality risk and long-term kidney complications, including hypertension, are associated with neonatal AKI. 10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 , 6 , 7 , 8 , 9 Short-term mortality risk and long-term kidney complications, including hypertension, are associated with neonatal AKI. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 11 Using these criteria, the prevalence and severity of AKI as well as the association of AKI with outcomes of interest in different neonatal populations and at different times after birth have been characterized. 10 A secondary analysis of a large cohort of ELBWs, who have the greatest risk of AKI among NICU patients, showed that stage 3 AKI (most severe) may portend subsequent mortality based on sCr concentration measurements collected as part of standard clinical care. 5 However, that study did not include longitudinal measures of organ dysfunction or shock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Neonatal Kidney Disease Improving Global Outcome (NKDIGO) criteria, the definition of neonatal AKI is currently based on two markers: serum creatinine (SCr) levels increase from a baseline steady state or reduced UO 10 11. Some limitation exists to use SCr in neonates due to the lack of baseline steady-state SCr in critically ill preterm neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric nephrology seems to take on this challenge, tailoring parameters to various specific demands, including those of the neonatal period, rare diseases, inherited disorders or peritoneal dialysis [ 7 , 8 , 9 , 10 ].…”
mentioning
confidence: 99%